Abraham Lincoln - Mara, Wil. (New York : Children's Press, 2002)
A brief overview of the life of the man who was President of the United States during the difficult years of the Civil War and who issued the Emancipation Proclamation freeing the slaves.
Includes index.
School Library Journal.
3.8
K-3
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents -- United States -- Biography; Presidents -- United States -- Biography